DEVELOPING CREATIVE THINKING IN GRADES 5–7 THROUGH STEP-BY-STEP ART EXERCISES - Boboqulov Javohir Hamzayevich (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article explores the pedagogical and methodological foundations of developing creative thinking among students in grades 5–7 through a step-by-step system of art exercises. The study emphasizes the role of sequential learning in fine arts education as a means of fostering imagination, aesthetic perception, and visual expression. By integrating modern pedagogical approaches such as the “flipped classroom,” project-based learning, and interactive art practices, the teaching process becomes more engaging and effective. The article highlights how gradual artistic training—starting from basic line and form exercises to complex compositional works—encourages students to think critically, experiment with artistic ideas, and express individuality through visual creativity. The findings suggest that systematic and creative methods in art lessons enhance students’ visual literacy, self-expression, and motivation to learn art as a form of communication and cultural understanding.